PP.48 The Impact of Severe Maternal Morbidity on Psychological Health at 6–8 Weeks Postpartum – a Prospective Cohort Study in England. (26th April 2013) - Furuta, M; Sandall, J; Bick, D
Abstract : Background: The incidence of severe maternal morbidity (SMM) is increasing in high-income countries as a consequence of higher caesarean section rates and more complex health needs of women who become pregnant. Access to emergency obstetric care means that for the majority of these women, SMM is unlikely to result in loss of life. However, little was known about the impact on postnatal morbidity. Aim: To assess the impact of SMM (defined as major obstetric haemorrhage, severe hypertensive disorders, critical care unit admission) on maternal health, focusing particularly on post-traumatic stress disorder (PTSD) symptoms at 6–8 weeks postpartum. Method: A prospective cohort study was undertaken of women who gave birth over six months in 2010 in one large inner city maternity unit in England. Data on health outcomes were collected on 1824 women using self-administered questionnaires at 6–8 weeks postpartum (response rate = 53%). Multivariable logistic regression analysis examined the relationship between SMM and PTSD symptoms taking into account factors that might influence the relationship. Ethics approval was obtained. Results: There was a higher risk of PTSD symptoms following SMM (OR = 3.22, 95%CI = 1.62–6.43, p = 0.001) after adjusting for all potential confounding factors. Women's higher perceived control during labour and birth and better neonatal outcomes slightly reduced the effect size of SMM on PTSD symptoms. Conclusion: Findings have important implications for women's health, and the content and organisation of maternity services. Women and clinicians should be aware that SMM can trigger symptoms of PTSD, with further work required to promote care to prevent these symptoms.